2016
DOI: 10.1093/mnras/stw2486
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and X-ray variability of active galactic nuclei withSwift

Abstract: We analyse a sample of 21 active galactic nuclei (AGN) using data from the Swift satellite to study the variability properties of the population in the X-ray, UV and optical band. We find that the variable part of the UV-optical emission has a spectrum consistent with a powerlaw, with an average index of −2.21±0.13, as would be expected from central illumination of a thin disc (index of −7/3). We also calculate the slope of a powerlaw from UV to X-ray variable emission, α OX,Var ; the average for this sample i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 134 publications
11
85
0
Order By: Relevance
“…We estimate a range for the bolometric luminosity of ∼ 0.3 − 3.0 L Edd (with the uncertainty mainly driven by the blackbody temperature adopted). This agrees with Sani et al (2010) and the average measurements of Buisson et al (2017) ) using an additional blackbody for the UV emission from thin disc.…”
Section: High Eddington Accretion?supporting
confidence: 89%
“…We estimate a range for the bolometric luminosity of ∼ 0.3 − 3.0 L Edd (with the uncertainty mainly driven by the blackbody temperature adopted). This agrees with Sani et al (2010) and the average measurements of Buisson et al (2017) ) using an additional blackbody for the UV emission from thin disc.…”
Section: High Eddington Accretion?supporting
confidence: 89%
“…4). Such lags favor the X-ray reprocessing scenario at accretion disk and have been reported in many AGNs where UV is found to be lagging behind X-ray emission as expected in the reprocessing scenario (e.g., Buisson et al 2017;McHardy et al 2014McHardy et al , 2018. Additional support for this comes from the general variability trend of OJ 287 where multi-wavelength variations are normally simultaneous on short timescales (Kushwaha et al 2018a(Kushwaha et al , 2013 with lag reported only when an additional emission component was competing with its general emission (Kushwaha et al 2018b).…”
Section: Radio-quiet Agn/disk Based Modelsmentioning
confidence: 61%
“…This is the equivalent to the disks being too big (the lag too large) by a factor of 1.6 based on the observed flux compared to the accretion disk model. More recently, observations of NGC2617 (Shappee et al 2014), NGC3516 (Noda et al 2016), NGC6814 (Troyer et al 2016), Fairall9 (Pal et al 2017), Ark120 (Gliozzi et al 2017), and a sample of 21 AGNs in the Swift archive (Buisson et al 2017) all find lags that are longer than expected for a standard thin disk. Both Pan-STARRS and the Dark Energy Survey (DES) are obtaining light curves of quasars in multiple photometric bands, allowing for determination of the average sizes from a large number of objects (Jiang et al 2017;Mudd et al 2017).…”
Section: Introductionmentioning
confidence: 98%